Blockchain Applicability for the Internet of Things: Performance and Scalability Challenges and Solutions - Ziaur Rahman (Electronics, 2022)
Blockchain has recently drawn wide attention in the research community. Since its emergence, the world has seen the expansion of this new technology, which was initially developed as a digital currency more than a decade ago. A self-administering ledger that ensures extensive data immutability over a peer-to-peer network has made it attractive for cybersecurity applications, including sensor-enabled Internet of Things (IoT) systems. Brand new challenges and questions now demand solutions, as IoT devices are now online in a distributed fashion to simplify our everyday lives. Motivated by those challenges, the work here has detailed issues from which an IoT infrastructure can suffer if the wrong blockchain technology is chosen. Unlike a typical review, this paper focuses on security challenges of the blockchain-IoT ecosystem through critical findings and applicable use cases. The contribution directs Blockchain architects, designers, and researchers in the domain to select an unblemished combination of Blockchain-powered IoT applications. In addition, the paper provides insight into the state-of-the-art Blockchain platforms, namely Ethereum, Hyperledger, and IOTA, to exhibit their respective challenges, their constraints, and their prospects in terms of performance and scalability.